USIA DAN KEGANDAAN OGLE-LMC 316/317 (THE AGE AND BINARITY OF OGLE-LMC 316/317) - Rhorom Priyatikanto (Lembaga Penerbangan dan Antariksa Nasional, 2017)
Large Magellanic Cloud (LMC) is a home of thousands of star clusters with various ages and metallicities. This galaxy also becomes the ideal laboratory for understanding binary cluster population which is large in number. One of the binary cluster candidates within the galaxy is OGLE-LMC 316/317 which is located near the bar of LMC. The age of OGLE-LMC 317 had not been determined, while the age of OGLE-LMC 316 was doubted. Whereas, age is an important parameter in the study of system binarity. In this study, photometry data from Optical Gravitational Lensing Experiment (OGLE) was used to construct color magnitude diagram and to estimate the age of OGLE-LMC 316/317. The results were the estimated ages of OGLE-LMC 316 and OGLE-LMC 317 which were 63 and 160 million years respectively. Based on these results, OGLE-LMC 316/317 system which has projected separation of 5 pc can be considered as primordial and coeval binary star cluster. ABSTRAK Large Magellanic Cloud (LMC) merupakan rumah bagi ribuan gugus bintang dengan beragam usia dan metalisitas. Galaksi ini juga menjadi laboratorium ideal untuk memahami populasi gugus ganda yang melimpah jumlahnya. Salah satu kandidat gugus ganda di dalamnya adalah OGLE-LMC 316/317 yang terletak di dekat batang LMC. Usia OGLE-LMC 317 belum diketahui, sementara usia OGLE-LMC 316 masih disangsikan. Padahal usia adalah parameter penting untuk mempelajari kegandaan dari sistem ini. Pada studi ini, data fotometri Optical Gravitational Lensing Experiment (OGLE) digunakan untuk membangun diagram warna magnitudo dan memperkirakan usia OGLE-LMC 316/317. Hasilnya, OGLE-LMC 316 diperkirakan berusia 63 juta tahun sementara OGLE-LMC 317 setidaknya berusia 160 juta tahun. Berdasarkan hasil ini, sistem OGLE-LMC 316/317 yang memiliki jarak pisah di bidang langit sebesar 5 pc dapat dianggap sebagai gugus ganda primordial dan coeval.